Assume the first integer is "x"
The next even integer would be "x + 2",
and after that, "x + 2 + 2" = "x + 4"
So,
(x) + (x + 2) + (x + 4) = 138
3x + 6 = 138
3x = 132
x = 44
The other numbers are 46 and 48
2007-03-30 10:50:19
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
Let's make the first integer in the series equal to x, the next even integer will be x + 2 and the even integer after that will be x + 2 + 2. So adding these together should give you 138 as follows:
x + (x+2) + (x+2+2) = 138
3x + 6 = 138
3x = 132
x = 44
So the numbers are 44, 46, 48.
2007-03-30 17:15:45
·
answer #2
·
answered by anastasios1979 1
·
6⤊
0⤋
x=the first integer
x+2=the second integer
x+4=the third integer
x+(x+2)+(x+4)=138
3x+6=138
3x=132
x=44
44+2=46
44+4=48
The integers are 44,46, and 48.
Check:
44+(44+2)+(44+4)=138
44+46+48=138
90+48=138
138=138
I hope this helps!
2007-03-30 18:25:21
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
2n-2 +2n +2n+2 = 6n= 138 so n= 23and the numbers are 44,46 and 48
2007-03-30 17:50:30
·
answer #4
·
answered by santmann2002 7
·
1⤊
0⤋